The Influence of Corporate Governance, Intellectual Capital and Corporate Social Responsibility on The Financial Performance of Pharmaceutical Companies on The Indonesia Stock Exchange - Suaidah, Yuniep Mujati (Journal of International Accounting, Taxation and Information Systems, 2024)
This study aims to test and prove the effect of corporate governance, intellectual capital, and Corporate Social Responsibility on the financial performance of the pharmaceutical sector. This research is descriptive and quantitative. Secondary data sources were used with documentation data collection techniques. The sampling technique was purposive sampling, with criteria including pharmaceutical sector companies that published complete financial reports from 2010 to 2023, resulting in a sample of 135 financial reports. The results indicate that corporate governance does not affect financial performance, implying that pharmaceutical companies are less able to build governance to improve financial performance. Intellectual capital affects financial performance, indicating that pharmaceutical sector companies can utilize resources to improve financial performance. Corporate Social Responsibility affects financial performance, meaning that the responsibilities carried out by companies in terms of economic, social, and environmental aspects can improve financial performance.